Misuse of PNPM Mandiri Rural Loan Funds (Case Study in Jorong Lubuak Batingkok) - Sukma Indah Darianti; Asyari Asyari; Hesi Eka Putri; Rusyaida Rusyaida (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Purpose – This study examines the misuse of revolving loan funds in the National Program for Community Empowerment in Rural Areas (PNPM Mandiri Perdesaan) within the Women's Savings and Loans Group (SPP) Usao Amai, Lima Puluh Kota Regency, and identifies contributing factors. Design/methodology/approach – A qualitative descriptive approach was employed, utilizing observation, semi-structured interviews, and documentation involving group members, administrators, and community leaders. Findings/Results – Revolving funds were primarily used for consumptive purposes—household expenses, education, medical costs, and debt repayment—rather than productive business activities. Despite this misuse, repayment rates remained stable due to strong social solidarity and mutual trust. Key factors contributing to misuse include weak supervision, low financial literacy, unstable household economies, and misperceptions of the program as flexible government assistance rather than business capital. Originality/Value – From an Islamic economics perspective, fund misuse deviates from principles of amanah (trustworthiness) and responsibility in managing qardh (loans), though members' commitment to repayment reflects enduring moral values. The study recommends strengthening supervision, providing financial literacy training, and integrating Islamic economic principles into community empowerment programs.